Life story of university students and the adjustment of living with motor deficiency - Maiara Suelen Mazera; Maria Itayra Coelho de Souza Padilha; Adriana Dutra Tholl; Soraia Dornelles Schoeller; Maria Manuela Ferreira Pereira da Silva Martins (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: To understand the life story of university students and the adjustment of living with motor deficiency. Method: A qualitative research, developed with eight university students with motor deficiency. Data collect was performed between October 2016 and March 2017. Thematic data analysis was used. Results: Two categories emerged: family as safe harbor and extra-family relationships: weaknesses and strengths. Family and friends were fundamental for facing disability, standing out for their support and affection. Friends have been encouraged to overcome the limitations and difficulties. Extra-family life was exposed to prejudice that resulted in fears and traumas. Conclusion: The impact of motor deficiency on daily life is the result of life experiences. Healthy family relationships, along with strong bonds of friendship, made the difficulties found in the daily life of these students smoother.